2013
DOI: 10.1016/j.neunet.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Using a million cell simulation of the cerebellum: Network scaling and task generality

Abstract: Several factors combine to make it feasible to build computer simulations of the cerebellum and to test them in biologically realistic ways. These simulations can be used to help understand the computational contributions of various cerebellar components, including the relevance of the enormous number of neurons in the granule cell layer. In previous work we have used a simulation containing 12000 granule cells to develop new predictions and to account for various aspects of eyelid conditioning, a form of moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…In contrast, neuroimaging studies have shown that cortical cerebellar and global cerebellar volumes are significantly reduced in patients with schizophrenia compared to healthy controls 36. As the cerebellum represents at least 10% of the brain volume that contains 50% of its neurons,37 it has been established that cerebellar cortical volume reduction is implicated in cognitive dysfunction in schizophrenia 36. Moreover, the aberrant network connecting the frontal cortex and cerebellum is believed to be involved in the development of cognitive dysfunction,38 because cerebellar stimulation dynamically influences the medial frontal cortex in mice and clinically alleviates cognitive dysfunction in patients with schizophrenia 39,40.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, neuroimaging studies have shown that cortical cerebellar and global cerebellar volumes are significantly reduced in patients with schizophrenia compared to healthy controls 36. As the cerebellum represents at least 10% of the brain volume that contains 50% of its neurons,37 it has been established that cerebellar cortical volume reduction is implicated in cognitive dysfunction in schizophrenia 36. Moreover, the aberrant network connecting the frontal cortex and cerebellum is believed to be involved in the development of cognitive dysfunction,38 because cerebellar stimulation dynamically influences the medial frontal cortex in mice and clinically alleviates cognitive dysfunction in patients with schizophrenia 39,40.…”
Section: Discussionmentioning
confidence: 98%
“…Lugaro cell activity also directly inhibits Purkinje neuron firing [33]. A single Lugaro cell makes inhibitory synaptic contact with about 150 nearby Golgi cells [31]; each Golgi cell makes inhibitory synaptic contact with about 3,000–5,000 granule cells [34]. Lugaro cell activity thus has the potential to reduce both the tonic and phasic components of Golgi cell inhibition onto large populations of granule cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in contrast to heat-evoked sensorimotor transformation which involves a hindbrain local circuit (Haesemeyer et al, 2018), the overall functional circuitry spans across the entire brain ( Figure 8), even though both studies observed strong response to heat in the telencephalon and the habenula (Figure 4). This input to the cerebellum could be further amplified by the divergent mapping of the mossy fiber input to the granular cells (Huang et al, 2013;Ito, 2006;Li et al, 2013) and then integrated at the Purkinje cell layer, which also receives excitatory input from the contralateral inferior olive (IO) through the climbing fibers (Ito, 2008). Purkinje cells modulate via inhibitory connections the output of the eurydendroid neurons which at the same time also receive direct excitatory connections from the granular cells (Ito, 2008) and feed into the ARTR, i.e.…”
Section: Discussionmentioning
confidence: 99%